Obligasi Bencana Alam Dengan Suku Bunga Stokastik Dan Pendekatan Campuran - Anggraini, Dian; Wijaya, Yasir (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
This study contains the group claims model as discussed by (Lee, 2007) for the pricing of natural disaster bonds. This research was conducted with several stages. First make the formula of bond price with stochastic interest rate and disaster event following non homogeneous poisson process. It further estimates the parameters of disaster loss data from the Insurance Information Institute (III) from 1989 to 2012 and interest rates from the Federal Reserve Bank. Because the determination of aggregate distribution is difficult to be exact, numerical calculation is done by mixed approach method (Gamma and Inverse Gaussian) to determine the solution of natural disaster bond price. Finally, shows how the impact of financial risk and disaster risk on the price of natural disaster bonds.